A Facile Magnetic Extrusion Method for Preparing Endosome‐Derived Vesicles for Cancer Drug Delivery (Adv. Funct. Mater. 44/2021). (26th October 2021) - Guo, Peng; Busatto, Sara; Huang, Jing; Morad, Golnaz; Moses, Marsha A.
Abstract : Endosome‐Derived Vesicles In article number 2008326, Peng Guo, Marsha A. Moses, and co‐workers develop a facile magnetic extrusion method to create endosome‐derived vesicles, called exosome mimetics (EMs), which share the same biological origin and similar morphology, composition, and biofunctions with native exosomes. The high yield and consistency of this magnetic extrusion method are important in overcoming one of the most significant manufacturing bottlenecks in exosome research.